The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.18632/aging.204256
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 inhibits ER stress induced apoptosis and improves diabetic cardiomyopathy by regulating PI3K/AKT/mTOR axis

Abstract: Objective: Extensive studies have shown that ERS may be implicated in the pathogenesis of DCM. We explored the therapeutic effects of lncRNAH19 on DCM and its effect on ERS-associated cardiomyocyte apoptosis. Methods: C57/BL-6j mice were randomly divided into 3 groups: non-DM group (controls), DM group (DCM), and lncRNAH19 overexpression group (DCM+H19 group). The effect of H19 on cardiac function was detected. The effect of H19 on cardiomyocyte apoptosis and cardiac fibrosis in DM was examined. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…However, it is unclear whether impaired MAMs after CIRI affect oxidative stress and autophagy through PI3K/AKT/mTOR. The modulation of the PI3K/AKT/mTOR pathway may be influenced by factors such as Ca 2+ transfer, ER stress, and mitochondrial function, all of which are closely associated with MAMs, highlighting the potential role of MAMs 55–57 . Therefore, we speculated that post‐CIRI MAMs might mediate oxidative stress and autophagy through PI3K/AKT/mTOR and verified it.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, it is unclear whether impaired MAMs after CIRI affect oxidative stress and autophagy through PI3K/AKT/mTOR. The modulation of the PI3K/AKT/mTOR pathway may be influenced by factors such as Ca 2+ transfer, ER stress, and mitochondrial function, all of which are closely associated with MAMs, highlighting the potential role of MAMs 55–57 . Therefore, we speculated that post‐CIRI MAMs might mediate oxidative stress and autophagy through PI3K/AKT/mTOR and verified it.…”
Section: Discussionmentioning
confidence: 63%
“…The modulation of the PI3K/AKT/mTOR pathway may be influenced by factors such as Ca 2+ transfer, ER stress, and mitochondrial function, all of which are closely associated with MAMs, highlighting the potential role of MAMs. 55 , 56 , 57 Therefore, we speculated that post‐CIRI MAMs might mediate oxidative stress and autophagy through PI3K/AKT/mTOR and verified it. The results show that the PI3K activator can partially reverse the aggravation of injury in CIRI mice induced by VAPB or PTPIP51 reduction, which is manifested by attenuating oxidative stress and autophagy, reducing cerebral infarction volume and improving neurological function.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These mutations have been found to be associated with myocardial fibrosis and cardiac dysfunction [27]. Additionally, studies have shown that excessive activation of PIK3CA and PIK3CB may lead to increased myocardial cell proliferation and inflammation, exacerbating the pathological process of DCM [28]. Playing a pivotal role in governing the progression of the cell cycle, particularly in cellular proliferation and division, CDK4 emerges as a vital protein [29].…”
Section: Discussionmentioning
confidence: 99%
“…55 Supplementary research has shown that lncRNA H19 through inhibition of PI3K/AKT/mTOR signaling pathways mediating effector molecules, such as p-PERK, p-IRE1 alpha, ATF6, CHOP and caspase cascade, inhibits the apoptosis pathway, thereby improving diabetic cardiomyopathy. 56 Hobuß et al used the H19 knockout mouse model to verify the regulatory role of lncRNA H19 in post-infarction myocardium, revealing its role in cellular mechanisms, including myocardial cell apoptosis and inflammatory response, leading to adverse cardiac remodeling. 57 In terms of modulating cardiac fibrosis, lncRNAs like LINC01013 have made strides, being recognized as potential novel regulators influencing the onset and progression of myocardial fibrosis.…”
Section: Lncrnasmentioning
confidence: 99%